2006
DOI: 10.1163/156856106775897748
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed laser deposition of hydroxyapatite-diamondlike carbon multilayer films and their adhesion aspects

Abstract: We have developed a layered hydroxyapatite/diamondlike carbon/functionally gradient diamondlike carbon-silver/titanium carbide/titanium carbonitride/titanium nitride composite film using pulsed laser deposition. A diamondlike carbon interlayer between a hydroxyapatite coating and the Ti-6Al-4V alloy can serve several purposes, including preventing corrosion of Ti-6Al-4V alloy, overcoming poor adhesion between the hydroxyapatite coating and the titanium oxide surface, and reducing inflammation at the implant/ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In spite of biological performance enhancements that HAp can provide to the Ti surface, there are still many concerns about the use of HAp coatings, especially with regard to long-term reliability [ 101 ]. Implant retrieval studies have shown remarkable degradation of HAp coatings over short implantation time due to the poor adhesion of HAp-Ti interface [ 101 , 102 ]. The mismatch in coefficient of thermal expansion (CTE) between HAp and Ti surface is the main reason for the poor adhesion [ 86 , 103 , 104 ].…”
Section: Sol-gel Deposition Of Hydroxyapatitementioning
confidence: 99%
“…In spite of biological performance enhancements that HAp can provide to the Ti surface, there are still many concerns about the use of HAp coatings, especially with regard to long-term reliability [ 101 ]. Implant retrieval studies have shown remarkable degradation of HAp coatings over short implantation time due to the poor adhesion of HAp-Ti interface [ 101 , 102 ]. The mismatch in coefficient of thermal expansion (CTE) between HAp and Ti surface is the main reason for the poor adhesion [ 86 , 103 , 104 ].…”
Section: Sol-gel Deposition Of Hydroxyapatitementioning
confidence: 99%
“…Another important trend that is emerging regarding ion-substituted hydroxyapatite thin films, is that of antibacterial coatings. To this regard, a wide range, and increasing amount, of literature is available about silver-doped hydroxyapatite, for which deposition by magnetron sputtering [74][75][76][77][78], PLD [79][80][81][82][83][84] and MAPLE [85] has been reported. Being the study of plasma assisted deposition of Ag-doped hydroxyapatite of more recent introduction, the majority of the studies focus on the influence of deposition parameters on the films characteristics and on the evaluation of antibacterial efficacy, while extensive, comparative in vivo studies are yet to be performed.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Moreover, it was recognized that R ku and R sk are parameters of key-importance when describing surface roughness of calcified tissue implants [84] because osteogenic cells' adhesion is sensitive to the stress concentrations which derive from the presence of sharp heights at the implant-tissue interface [85], likewise they can be considered against bacterial proliferation [86]. Inferred values for skewness and kurtosis parameters indicated a sharper heights (R ku~5 .6) distribution of surface features in case of Li-P structures as compared with Li-0 and Li-C ones (R ku~3 .1 and~3.5), with more peaks than valleys (R sk > 0) and that these peaks and valleys are much closer in height and depth for Li-P coatings (R sk~0 .17) than those of Li-0 and Li-C (R sk of 0.46 and 0.56, respectively).…”
Section: Possible Mechanisms Explaining the Antimicrobial Activity Of Synthesized Structuresmentioning
confidence: 99%